Stability and controlled release enhancement of Labisia pumila's polyphenols - Afiqah, Yeop; Jessinta, Sandanasamy; Pang, Sook Fun; Jolius, Gimbun (Elsevier, 2021)
The thermal stability and controlled release of Labisia pumila's polyphenols was increased using a surface protein encapsulated microcapsule. The polyphenols were measured using an ultra-performance liquid chromatography, whereas the degradation mechanism was elucidated using a mass spectroscopy analysis. The microencapsulation increased the polyphenols retention from 29.9 (without encapsulation) to 92.1 with spray drying. The mixture of gum Arabic and whey protein isolate 9:1 gave the best retention of gallic acid (95.2), protocatechuic acid (91.2), epigallocatechin (86.0) and rutin (95.9) with an average polyphenol retention of 92.1. The X-ray photoelectron spectroscopy analysis showed the formation of surface protein that acted as a protective layer, which increased the polyphenols stability. Decarboxylation was the primary degradation mechanism for gallic acid and protocatechuic acid, while rutin underwent hydrolysis. The degradation of epigallocatechin was due to deprotonation or dehydroxylation. The microcapsule with surface protein increased the overall polyphenols release with the simulated gastric and intestinal conditions by ~5 with an average release of 96.3. The polyphenols release kinetics was analysed using Baker-Lonsdale, Korsmeyer, Higuchi, and Hixson-Crowell models. The release mechanism of the polyphenols best fit the Hixson-Crowell model indicating a surface erosion dependent release.